2015
DOI: 10.1177/1936724415589633
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Challenge

Abstract: Research on drug courts over the past decades has focused primarily on individual predictors of success and/or has examined the effectiveness of various judicial as well as therapeutic intervention strategies. To broaden our understanding of recovery as it occurs within the context of social networks, the following paper discusses the application of a new network-based framework of recovery capital. Participants in a small rural southeastern Adult Drug Court filled out a series of questionnaires and participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Laudet (2011) asserts that quality-of-life measures may enhance recovery studies by providing another index of success aside from substance use abstinence. In addition, Zschau et al (2015) suggest that drug court participants are limited in their access to networks outside of their therapeutic communities and that this situation might restrict social capital accumulation. Although we did not directly assess quality of life or other human capital accumulation in our study, we might presume that legal employment and the termination of sex work would enhance both (Hsiao et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Laudet (2011) asserts that quality-of-life measures may enhance recovery studies by providing another index of success aside from substance use abstinence. In addition, Zschau et al (2015) suggest that drug court participants are limited in their access to networks outside of their therapeutic communities and that this situation might restrict social capital accumulation. Although we did not directly assess quality of life or other human capital accumulation in our study, we might presume that legal employment and the termination of sex work would enhance both (Hsiao et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…While not everyone who is isolated becomes lonely, people with substance use problems may be more vulnerable due to stigma and a rearrangement of social networks once they engage with recovery services. Literature suggests that recovery is dependent on the formation of strong social networks, yet many in this sample offered a description of recovery as an isolating and lonely experience (Kawachi et al, 2004;Zschau et al, 2016) During COVID-19, it has been argued that prolonged stay at home efforts are likely to severely increase isolation, social disconnection and loneliness (Zixin and Wang, 2020). This research supports these arguments, but also highlights the individualised impact of these conditions on recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has demonstrated that mental illness and problem substance use often result in the erosion of close social networks (Zschau et al, 2016). Moreover, the individual belief of not belonging to the wider community also compound feelings of isolation and loneliness in this population (Copeland et al, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…Many women have bemoaned the flaws of a drug court system that often result in recidivism and broken families (Kilgore, 2015). Systemic hurdles undermine women's health and wellness (D. S. Morse et al, 2015), and the court often fails to help women access natural family support networks (Zschau et al, 2016). Liang et al (2016) advised drug courts to deviate from the "one-size-fits-all" (p. 285) model to create programs tailored to the needs of the individual and that seek participant input to create best practices.…”
Section: Criminal Justice Service Providers and Stigmamentioning
confidence: 99%